2011
DOI: 10.3390/d3010091
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Climate Change on Recent Vegetation Changes on Dovrefjell, Norway

Abstract: Abstract:The ongoing climate warming has been reported to affect a broad range of organisms, and mountain ecosystems are considered to be particularly sensitive because they are limited by low temperatures. Meteorological data show an increased temperature for the alpine areas at Dovrefjell, Norway, causing a prolonged growing season and increased temperature sum. As part of the worldwide project Global Observation Research Initiative in Alpine Environments (GLORIA), the short-term changes in vascular plant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Venn et al (2012) found that species numbers of shrubs and graminoids increased whereas number of herbs decreased at mountains in Australia. Similarly, Michelsen et al (2011) found increased abundance of some shrubs and graminoids in Dovrefjell, Norway. In our study, we predicted higher species numbers in all functional groups except seedless plants.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Venn et al (2012) found that species numbers of shrubs and graminoids increased whereas number of herbs decreased at mountains in Australia. Similarly, Michelsen et al (2011) found increased abundance of some shrubs and graminoids in Dovrefjell, Norway. In our study, we predicted higher species numbers in all functional groups except seedless plants.…”
Section: Discussionmentioning
confidence: 72%
“…According to Gottfried et al (2012), the Dovrefjell mountain region differed from other European mountains in rate of vegetation change, being the only region where thermophilous species had not increased. The degree of climate change has been relatively moderate in this region compared to other European regions (Michelsen et al 2011;Wehn et al 2012), as well as compared to other mountain regions along the coast-inland transect in central Norway (Tveito and Dyrrdal 2011).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Decrease in species number was rarely recorded during the monitoring of the Central Alps (Gottfried et al, 1998;Grabherr et al, 2001;Walther et al, 2005), with the exception of the decline of nival and subnival species resulting from the expanding growth of alpine species (Klanderud and Birks, 2003;Pauli et al, 2007). Increase of species richness at lower altitudes was also recorded (Michelsen et al, 2011). The percentage of newcomer species was highest on the southern slope, except for the subnival zone, with the highest number of newcomer species toward the western compass direction (Figure 3).…”
Section: Indicator Speciesmentioning
confidence: 96%